B-LEARNING y su incidencia en los procesos educativos en los estudiantes de la carrera de Pedagogía de las ciencias experimentales informática, de la Universidad Técnica de Babahoyo, diciembre 2022 - abril 2023 - Onofre Chiriguayo, Jennifer Maoli (2023)
The objective of the scientific research was to analyze the incidence of B-Learning in the education of students of Pedagogy of Experimental Sciences and Informatics at the Technical University of Babahoyo. A survey was applied to 129 students and a descriptive and quantitative methodology was used to obtain the results. The findings showed that most students accept the use of technological tools in education and consider that B-Learning allows creating more flexible pedagogical spaces and integrating various digital resources in teaching. However, there was a small percentage of students who disagreed with these ideas, suggesting the need to continue exploring and evaluating the use of these tools in education. It is concluded that the use of digital tools in education is important to improve the quality of learning and it is recommended that teachers take advantage of B-Learning platforms and the use of multimedia in their classes.